The Use Of Literary Texts In Efl Classrooms To Promote Character Education - Sri Mulyani (el-Idarah: Jurnal Manajemen Pendidikan Islam, 2019)
This paper proposes the use of literature in EFL (English as a Foreign Language) classrooms to promote character education. It reviews briefly theoretical issues on character education and teaching English through literature. Guidelines are given for the use of literature in the language classroom. Finally, this paper presents the technical application of teaching and learning through literary texts to promote character education.